Can Workshops Provide a Way to Enhance Patient/Client Centered Collaborative Teams?: Evidence of Outcomes from TEAMc Online Facilitator Training and Team Workshops - Orchard, Carole; Bursey, Susan; Peterson, Linda; Verrilli, Susan (International Journal of Practice-based Learning in Health and Social Care, 2016)
The movement towards collaborative interprofessional teamwork for improving patient care has sometimes been impeded by health providers who have a desire to work together, but are unsure how to move towards such models of care delivery. The situation can be complicated by some reluctance on the part of health care institutions to release staff from normal duties to participate in team building training. The purpose of this study was to report on a collaborative team building process supported by the hospital administration in northern Ontario, Canada, and to provide evaluation results for the Toolkit for Enhancing and Maintaining Team Collaboration (TEAMc) using measurements before the start, at the end of the workshop series and at eight months post-series. Participants were from two teams (Acute Care and Rehabilitation) in a northern Ontario, Canada, hospital. TEAMc was comprised of six, 3-hour workshops offered over six months in 2014/15. A total of 77 health providers completed the pre-intervention Interprofessional Socialization & Valuing Scale (ISVS) and the Assessment of Interprofessional Team Collaboration Scale (AITCS), 50 health providers completed the post-intervention instruments and 32 and at the eight month follow-up. The study found that TEAMc can result in changes in team members’ socialization towards wanting to participate in interprofessional teams and in the team’s ability to emulate interprofessional client-centered collaborative practice. The greatest learning gained by participants was around their role clarification and understanding of each other’s roles and expertise, as well as developing their capacity to use a process to resolve interprofessional conflicts.